Bacteriological Studies on Johne's Disease in Cattle and Sheep - Taylor, Alexander Wilson (The University of Edinburgh, 1953)
Much of the fundamental knowledge of Johne's disease was provided in this country by Twort and Ingram, who first succeeded in cultivating the causal organism, and by McFadyean and his co- workers in the years prior to 1920. During the succeeding years the disease has presented a problem of gradually increasing importance, a process which has recently been greatly accelerated by the development of means to control or greatly to diminish, if not always to eradicate, the major infectious diseases of cattle in this country. Of these so- called major diseases, namely tuberculosis, contagious abortion and streptococcal mastitis, Johne's Disease alone still provides a serious problem to veterinary science and to agriculture. The work described in this thesis was undertaken over a period of rather more than ten years, first at the Animal Diseases Research Association, Moredun Institute, Edinburgh, and later at the Agricultural Research Council Field Station, Compton, Berkshire, and the papers, although not in chronological order, may conveniently be presented in three parts. I. A study of Johne's disease in sheep, consisting of four papers: - "Ovine paratuberculosis (Johne's disease of sheep) ". (Thesis - page 6) J. comp. Path. 55. 41 191+5 • "Observations on the isolation of Mycobacterium johnei in primary culture ". (Thesis - page 13) J. Path. Bact. 62. 647. 1950 • "Varieties of Mycobacterium johnei isolated from sheep ". (Thesis - page 21) J. Path. Bat. 63. 333. 1951 • "The experimental infection of cattle with varieties of Mycobacterium johnei isolated from sheep ". (Thesis - page 29) In press These papers have provided a new conception of the bacteriology of Johne's disease as it affects sheep. The disease has been shown to be caused in this country by one of two distinct organisms, the classical type of M. johnei and a highly pigmented organism, apparently a variant of the classical type. This variant, with the organism causing Johne's disease in sheep in Iceland, was originally regarded as uncultivable, but ...